On the stability of thin plates subjected to biaxial compressions of complex loading - Dung, Dao Van (Vietnam Journal of Mechanics, 1993)
In this paper, the method for calculating an expression of critical forces in general case has been presented. As for its application, using computer programming in Pascal we've found the value of critical forces. The influence of complex loading on the stability of plates has been studied.